82 Late-Breaking: Effects of Solvent- or Mechanically Extracted-Carinata Meal On Intake And Total-Tract Digestibility In Cows Fed Long-stem Or Ground Corn Residues. (7th December 2018) - Brake, D; Rosenthal, E; Perry, G
Abstract: Carinata meal is a residue created during the manufacture of aviation biofuel from Brassica carinata. Cows fed long-stem or ground corn residues were individually supplemented mechanically- or solvent-extracted carinata meal or canola meal (positive control) to determine effects of carinata meal on nutrient digestion and intake when ruminal fermentation is limited by ruminally available N (RAN). Intake of supplemental protein was complete among cows fed solvent-extracted carinata meal and canola meal, but intake of mechanically-extracted carinata meal was less (14.0% of DM offered). Glucosinolate concentration in mechanically-extracted carinata meal (72.34 mmol/g) was much greater (P < 0.01) than concentrations in solvent-extracted carinata meal (16.51 mmol/g) or canola meal (1.57 mmol/g), and glucosinolate concentration was negatively correlated (r2 = -0.74) to intake of supplemental protein. Typically, intake is reduced among forage fed cattle when RAN limits ruminal fermentation. Forage intake tended (P = 0.10) to be greatest among cows fed canola meal, least for cows not provided supplemental protein and forage intake was intermediate for cows fed solvent- and mechanically-extracted carinata meal. Further, forage intake was greater (P < 0.01) in cows fed long-stem corn residue compared to cows fed ground corn residue. Measures of total-tract DM (P = 0.28), OM (P = 0.22), NDF (P = 0.30) and ADF (P = 0.18) digestibility were not affected by supplemental protein. However, total-tract digestion of DM, OM, NDF, and ADF were increased (P < 0.01) more than 23% among cows fed long-stem compared to ground corn residue. Apparently, increased intake of forage in response to supplemental protein counteracted potential increases in total-tract digestion. These data seem to suggest that carinata meal can be useful as supplemental protein to cattle fed forage; however, utility of carinata meal may be affected by different processing methods and residual concentrations of glucosinolates.